Superficial Calcification With Rotund Shape Is Associated With Carotid Plaque Rupture: An Optical Coherence Tomography Study - Shi, Xuan; Han, Yunfei; Li, Min; Yin, Qin; Liu, Rui; Wang, Fang; Xu, Xiaohui; Xiong, Yunyun; Ye, Ruidong; Liu, Xinfeng (Frontiers in Neurology, 2020)
Background: Plaque rupture is an important etiology for symptomatic carotid stenosis. The role of calcification in the plaque vulnerability has been controversial. We aimed to detect the geometric features of calcifications in carotid plaque and to examine its association with plaque rupture. Methods: Optical coherence tomography assessment of carotid plaque was performed in 88 patients. Calcification shape was evaluated through quantitative measurements of the long and short axis, area size, circumference, calcification arc, and longitudinal length. Calcification location was analyzed through the distance to the lumen. Furthermore, we developed idealized fluid-structure interaction models to investigate the association of calcification shape and plaque stress. Results: A total of 33 ruptured plaques and 30 non-ruptured plaques were recognized. Ruptured plaques had more multiple calcifications and protruded calcifications. The calcifications in the ruptured plaques displayed a remarkably lower long-axis/short-axis (L/S) ratio than in the non-ruptured plaques (p = 0.001). We classified calcification shape into crescentic calcification (L/S > 2.5) and rotund calcification (L/S ≤ 2.5). Rotund-shaped calcifications were more common in ruptured plaques than in non-ruptured plaques (p = 0.02). Superficial calcifications with minimal distance to the lumen ≤ 50 μm accounted for 79.4% of all calcifications in the ruptured plaques, and only 7.7% in the non-ruptured plaques (p < 0.001). Biomechanical analysis showed that the plaque with rotund-shaped calcification developed 7.91-fold higher von Mises stress than the plaque with crescentic calcification. Conclusions: Superficial calcifications and rotund-shaped calcifications are associated with carotid plaque rupture, suggesting that calcification location and shape may play a key role in plaque vulnerability.